THE OPTIMISED CONDITIONS OF INDUCTION OF RECOMBINANT RIP rMJC15310 ACTIVITY ISOLATED FROM Mirabilis jalapa L. LEAVES - Astuti, Puji; ., Sudjadi; ., Sismindari (INDONESIAN JOURNAL OF PHARMACY, 2012)
Ribosome Inactivating Proteins (RIPs) are compounds isolated from plants with ability to inhibit protein synthesis. The inhibition of protein synthesis is due to inactivation of ribosomal RNA through a site-specific  deadenylation  mediated  by  RNA  N-glycosidase. Reportedly, RIPs mainly possess wide range of bioactivity including antiviral  activity  against  plant  infections.  Other  activities  of  RIP were  as  abortifacien,  antivirus  and  anticancer.  This  study  was aimed  to  isolate  and  characterize  the  optimum  conditions  for inducing  the  expression  of  recombinant  RIPs  isolated  from  the leaves  of  Mirabilis  Jalapa  L.  We  have  been  successfully  isolated several  RIPs  and  engineered  these  proteins  to  be  expressed  in  E. coli. These recombinant proteins were obtained by screening cDNA library  originated  from  the  mRNA  of  Mirabilis  jalapa  L  leaves,  and inserted  into  pUC19  carrying  lacZ  gene.  The  presence  of recombinant  plasmid  was  tested  by  using  α-complementation assay. Many RIPs have been isolated from plants and these proteins express  enzymatic  activity  by  cutting  supercoiled  double  stranded DNA. One RIP namely rMJC15310 was obtained from this study and the  proteins  having  ~  8kb  in  size,  cut  the  supercoiled  DNA  into linear  form  at  the  concentration  as  low  as  5  µg.  The  ability  to  cut supercoiled  DNA  increased  on  inducing  its  expression  with  0.4% IPTG.Key words:   Ribosome  Inactivating  Proteins  (RIP),  IPTG,  Mirabilis  jalapa L., recombinant protein